Tracing European structured finance counterparty networks - Adrien Amzallag; Maximilian L. Blau (European Central Bank (ECB), 2017)
Asset-backed securities (ABSs) and covered bonds (CBs) are structured finance instruments that require a range of key services, which may be provided by many firms. However, despite the prevalence of structured finance instruments in Europe, the network between issuers and service providers has to date remained unexplored. This paper traces and describes these connections, using a new database covering the majority of public ABSs and CBs outstanding between August 2008 and March 2017. It appears that ABS and CB issuers are highly reliant on affiliated counterparties ("close links") to provide the above-mentioned key services, especially when programmes are larger and/or are retained by the issuer for use as collateral with the Eurosystem. When only "non-close links" across banking groups are considered, instances of reliance on just a few service providers have gradually decreased in number, with a more balanced system developing over time. The paper finds similar results for networks based on the use of securities as Eurosystem collateral. These findings help demonstrate the importance of the Eurosystem's risk management framework for ABSs and CBs, and support the orientation of recent regulatory efforts at the European level.
Keywords: G32; D85; G21; G23; 330; structured finance; asset-backed securities; covered bonds; networkanalysis; collateral; financial regulation